Inorganic Element Determination of Romanian Populus nigra L. Buds Extract and In Vitro Antiproliferative and Pro-Apoptotic Evaluation on A549 Human Lung Cancer Cell Line - Brigitta Kis; Ioana Zinuca Pavel; Daniela Haidu; Mariana Nela Ștefănuț; Zorița Diaconeasa; Elena-Alina Moacă; Cristina Adriana Dehelean; Simona Șipos; Alexandra Ivan; Corina Danciu (MDPI AG, 2021)
Populus nigra L. is a plant from Salicaceae family, native in Europe. Many parts of this tree can be used as active ingredients, but the most valuable are the buds. In recent years, a growing number of studies reported their activity in the development of a wide range of pharmacological activities including diabetes, cardiovascular diseases, and cancer. The aim of this study was to determine the phytochemical composition and to evaluate the inorganic elements' concentration as well as the in vitro antiproliferative and pro-apoptotic potential of a Populus nigra L. buds extract collected from Timișoara (Romania) against A549 human lung cancer cell line. Populus nigra L. bud extract was found to contain twelve different phenolic compounds. The inorganic elements concentrations were below the limit of detection for Co, Pb, and As, whereas Cu = 6.66 µg/g; Cr = 0.79 µg/g; Ni = 3.28 µg/g; Fe = 39.00 µg/g; Zn = 14.84 µg/g; Mn = 0.59 µg/g; Al = 2109.87 µg/g; and Cd = 0.019 µg/g. The extract was tested for the in vitro antiproliferative and pro-apoptotic potential on A549 human lung cancer cell line using different concentrations, namely 10, 25, 50, 75, 100, and 150 μg/mL. Results have shown that poplar bud extract induced a significant decrease of tumor cell viability in a dose-dependent manner with an IC50 = 72.49 μg/mL and blocked the cells in the G0/G1 phase of the cell cycle. Phenomena of early apoptosis (from 1.34 ± 0.33% control cells to 2.68 ± 0.62% at 150 µg/mL) and late apoptosis (from 1.43 ± 0.14% control cells to 5.15 ± 1.02% at 150 µg/mL) were detected by Annexin V-PI double staining. Poplar bud extract can be regarded as a promising candidate for future studies involving lung cancer.